Pembuatan dan Uji Kualitas Sabun Transparan dengan Bahan Aktif Ekstrak Kulit Kayu Bangkal (Nauclea subdita) Khas Kalimantan Selatan - Amalia Fateha Rahmad; Sybilla Natasya; Tuty Al Wiah H.J; Syinta Febriyanti Aufa; Kholifatu Rosyidah (Jurnal Natural Scientiae, 2025)
The use of synthetic soaps containing harmful ingredients has driven consumers toward natural soap alternatives. Transparent soap offers the advantage of producing a softer lather and containing moisturizing agents that help prevent dry skin, making the development of transparent soaps with natural active ingredients essential for maintaining skin health and beauty. This study aimed to develop a transparent soap formulated with bangkal wood bark (Nauclea subdita) extract, a native plant of South Kalimantan rich in secondary metabolites such as alkaloids, flavonoids, polyphenols, and saponins. Previous studies have reported that these compounds possess natural antioxidant and sunscreen properties, as well as anti-inflammatory, antiplasmodial, antipyretic, and antimicrobial potentials. The methodology included reflux extraction using 96% ethanol, soap formulation through saponification, and comprehensive quality evaluation. Tests conducted included measurements of water content, pH, chloride content, ethanol-insoluble matter, free fatty acids/alkali, total fatty matter, unsaponified fat, foam stability, and organoleptic properties. The results showed that the transparent soaps with bangkal wood bark extract met the SNI 3532:2021 standards for water content, pH, ethanol insoluble matter, chloride content, foam stability, and total fatty matter across all extract concentrations. However, soap D (6 grams extract) exceeded the acceptable limit for free fatty acids. Organoleptic evaluation indicated that all formulations were well accepted by the panelists. Therefore, the bangkal wood bark extract demonstrates strong potential as a natural active ingredient for developing transparent soap formulations that meet quality standards.